TO EVALUATE THE CARDIOPROTECTIVE AND ANTI-OXIDANT EFFECT OF METHANOLIC EXTRACT OF THE LEAVES OF TRIBULUS TERRESTRIS IN WISTAR RATS - BARAKA, BABIKER BASHIR HAROUN; V RAO, BHAGYA; PKM, NAGARATHNA; JHA, DEEPAK KUMAR; VARDHINI N, HARSHA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the current study was to evaluate the cardio protective and anti-oxidant effect of methanolic extract of the leaves of Tribulus terrestris (TT) in Wistar Rats. Methods: Extracted leaves of TT were evaluated for cardioprotective and antioxidant activities in in vivo model. Thirty rats were divided into 5 groups. Group I and II served as normal control and disease control (doxorubicin 20 mg/kg I.P.), respectively, while Group III was the treated group with standard drug (vitamin-E 10 mg/kg P.O). Group IV and V served as the test groups, which were pre-treated with 250 mg/kg and 500 mg/kg body weight per day of “TT,” and the treatment was given for 7 days, On the 5th day, doxorubicin was given I.P 20 mg/kg, then 48 h after I.P of doxorubicin, animals were sacrifice and then blood samples was taken for biochemical estimation, and the rat heart for histopathological examination. Along with it, antioxidant studies were carried out using heart tissue homogenate from each group. Results: The administration of doxorubicin to control group’s rats presented a significant increase in serum total cholesterol (TC), triglycerides (TGs), low-density lipoprotein, creatine kinase-MB, serum glutamic-oxaloacetic transaminase (SGOT), serum glutamic-pyruvic transaminase (SGPT), and decrease in high-density lipoprotein (HDL). Rats treated with TT showed decreased TCs, TGs, low-density lipoprotein, CKMB, SGOT, SGPT, and increases HDL levels. The histopathological studies also showed that the TT significantly minimized the damage induced by doxorubicin. Conclusion: It can be concluded that the TT could be a potential candidate for the treatment of cardiotoxicity.